The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s40814-021-00953-6
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing technology to enable all women mobility in labour and birth: feasibility of implementing beltless non-invasive fetal ECG applying the NASSS framework

Abstract: Background A new wireless and beltless monitoring device utilising fetal and maternal electrocardiography (ECG) and uterine electromyography, known as ‘non-invasive fetal ECG’ (NIFECG) was registered for clinical use in Australia in 2018. The safety and reliability of NIFECG has been demonstrated in controlled settings for short periods during labour. As far as we are aware, at the time our study commenced, this was globally the first trial of such a device in an authentic clinical setting for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
(23 reference statements)
0
10
0
Order By: Relevance
“…18,26 In addition, reported skin irritation from the electrodes does not prevent women from reusing the NI-FECG. 20,27 The aforementioned studies evaluated several NI-FECG devices: Avalon-Beltless, 27 Femom, 4…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,26 In addition, reported skin irritation from the electrodes does not prevent women from reusing the NI-FECG. 20,27 The aforementioned studies evaluated several NI-FECG devices: Avalon-Beltless, 27 Femom, 4…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that women prefer the comfort of the NI‐FECG device over the DU device 18,26 . In addition, reported skin irritation from the electrodes does not prevent women from reusing the NI‐FECG 20,27 . The aforementioned studies evaluated several NI‐FECG devices: Avalon‐Beltless, 27 Femom, 4 Monica‐AN24, 17,20,21,25,26 Monica‐Novii 18,19 and Nemo 23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Existing literature on a similar NIFECG device (Monica AN24, Monica Healthcare, Nottingham, UK) using the same signal acceptance criteria have reported a success rate as low as 49% of the collected traces meeting this criteria 19–21. Moreover, we estimate an additional 30% trace exclusion due to technical issues arising from using a novel device 22. Therefore, we anticipate that we will need to recruit 200 participants to obtain 100 participants with interpretable and informative traces.…”
Section: Methodsmentioning
confidence: 99%
“…[19][20][21] Moreover, we estimate an additional 30% trace exclusion due to technical issues arising from using a novel device. 22 Therefore, we anticipate that we will need to recruit 200 participants to obtain 100 participants with interpretable and informative traces. Open access…”
Section: Sample Sizementioning
confidence: 99%
“…CEFM involves the use of electronic devices to monitor the fetal heart rate and uterine contractions continuously throughout labour [ 1 ]. CEFM may be conducted via a cardiotocograph (CTG) either in wired, or wireless forms, internal scalp electrode (FSE) which involves a spiral electrode being inserted into the fetal scalp or breech [ 2 , 3 ], or non-invasive fetal electrocardiogram (NIFECG), a wireless and beltless monitoring device which has more recently become available on the Australian market [ 4 ]. All forms of CEFM provide real-time information on the fetal heart rate pattern in conjunction with the measurement of uterine activity.…”
Section: Introductionmentioning
confidence: 99%